2010
DOI: 10.1111/j.1365-2958.2010.07424.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulating cellular recombination potential through alterations in RecA structure and regulation

Abstract: SummaryThe wild-type Escherichia coli RecA protein is a recombinase platform with unrealized recombination potential. We have explored the factors affecting recombination during conjugation with a quantitative assay. Regulatory proteins that affect RecA function have the capacity to increase or decrease recombination frequencies by factors up to sixfold. Autoinhibition by the RecA C-terminus can affect recombination frequency by factors up to fourfold. The greatest changes in recombination frequency measured h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 93 publications
0
32
0
Order By: Relevance
“…The variations are sometimes subtle and sometimes not [19, 8487]. The same theme is highlighted in recent work demonstrating substantial improvements in the capacity of some mutant variants of E. coli RecA protein to promote conjugational recombination [88]. Most important, the variations do not reflect an evolutionary approach to some common and most efficient platform for DNA pairing and strand exchange.…”
Section: Discussionmentioning
confidence: 99%
“…The variations are sometimes subtle and sometimes not [19, 8487]. The same theme is highlighted in recent work demonstrating substantial improvements in the capacity of some mutant variants of E. coli RecA protein to promote conjugational recombination [88]. Most important, the variations do not reflect an evolutionary approach to some common and most efficient platform for DNA pairing and strand exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Some RecA mutant proteins are less inhibited by RecX protein. There is only a slight decrease in the rate of ATP hydrolysis of the RecA4C17 protein or RecAD112R protein at high RecX concentration [14,15]. Previously we showed that RecX and SSB act as functional antagonists; i.e., the inhibitory effect of RecX on RecA decreases substantially in the presence of SSB [16].…”
Section: Introductionmentioning
confidence: 95%
“…The frequency of meiotic recombination in the aw-wv segment in the F 1 RecA plants is 46.7%, which is 1.2 times higher than in the corresponding non transgenic hybrids (39.6%) ( Table 6). However, like in the case of the wv d segment, the rf value for the aw wv region does not exceed the rf values in the non transgenic Marglob × Mo938 hybrids (Tables 4 and 6).…”
Section: 4mentioning
confidence: 92%
“…It has become known recently that the deletion of several amino acid residues of the C end of the E. coli RecA protein leads to a 4.3 fold enhancement of its activity [46]. It is possible that the fusion of RecA at the C end with the lichenase reporter protein LicBM3 in the hybrid protein NLS RecA LicBM3 caused a decay of its activity and resulted in the absence of any effect in the F 1 NLS RecA LicBM3 plants.…”
Section: 4mentioning
confidence: 99%